(3GdeNJUQ GdeajO aj Yde GdJGQjNs - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s ((3jMji Hf eMeO Hf GdOeSjfi GdTGaYi s)
(3ChdgG (B:s
(3hHYO aEf ef LedI GdYdhe GdfGaYg ai GdeHOC hGdeYGO heG HjfgG Yde GdJGQjN GdPi ahGFOg hZQGFHg dGJYO hdGJMUi s
(3BNQgG (B:s
(3MUd GdaQGZ ef JQJjH gPG GdfeNJUQ ai Yde GdJGQjN s
(3GfXQ GjVG HQbe (B458s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B150s
Keywords: (3GdJGQjNs